Alendronate Prevents Early Periprosthetic Bone Loss in Cementless Total Hip Arthroplasty Better Than Simvastatin - Dragos Apostu; Daniel Oltean-Dan; Alexandru Mester; Andrei Maxim; Adrian Bogdan Tigu; Horea Rares Ciprian Benea; Dan Cosma; Doina Piciu (Applied Sciences, 2022)
Background and Objectives: Cementless total hip arthroplasty leads to an early periprosthetic bone loss, which can impair the osseointegration process and lead to a femoral implant migration during early weight-bearing. An altered osseointegration process can lead to aseptic loosening, which is the most frequent late complication in these surgical procedures. The objective of this study was to compare the effect of alendronate and simvastatin in the prevention of early periprosthetic bone loss found in osteoporotic patients. This can lead to earlier weight-bearing in patients, as well as reduce the rate of aseptic loosening. Materials and Methods: Forty-five patients undergoing cementless total hip arthroplasty were equally distributed into three groups: group I (alendronate), group II (simvastatin), and group III (control). The alendronate group received 5 mg of alendronate postoperatively, daily for 8 weeks, and the simvastatin group received 20 mg daily for 4 weeks postoperatively, followed by 40 mg daily for 4 weeks. We determined bone mineral density (BMD), as well as bone serum markers beta cross-laps (β-CTx) and alkaline phosphatase (ALPL) preoperatively, 4 weeks postoperatively, and 8 weeks postoperatively. All patients were not allowed to fully bear weight for 6 weeks postoperatively. Results: Alendronate statistically significantly increases the BMD at one month postoperatively compared to the control group in Gruen zones 5 and 6 (p = 0.042 and p = 0.039). Overall, the BMD was higher in the alendronate group compared to the control group at one month postoperatively (p = 0.043). Alendronate decreased β-CTx bone serum marker compared to control at one month and two months (p = 0.024 and p = 0.012). Moreover, alendronate showed a higher decrease in β-CTx compared to simvastatin at both timelines (p = 0.028 and p = 0.03, respectively). Conclusions: The study shows that alendronate administration following cementless total hip arthroplasty offers better protection against periprosthetic bone loss compared to simvastatin.